Рівень фізичної активності студентів вищих навчальних закладів - Анатолій Цьось; Юзеф Бергєр; Олександр Сабіров; Anatoly Tsos; Jozef Berhyer; Alexander Sabirov (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Завдання роботи – визначення рівня фізичної активності студентів вищих навчальних закладів. Серед матодів – методика The International Physical Activity Questionnaire (IPAQ) (міжнародний опитувальник фізичної активності). Усього в педагогічному досліджені брало участь 395 студентів (хлопців) 1–4 курсів Objectives work – determining the level of physical activity of students in higher education. Among matodiv – methodology The International Physical Activity Questionnaire (IPAQ) (International Physical Activity Questionnaire). All in educational research involved 395 students (boys) 1–4 courses full-time Eastern National University and Lesi Ukrainian National University «Kyiv Polytechnic Institute». Most respondents (66.3%) observed low levels of physical activity. Almost a quarter of respondents (26,9 %) have an average level of physical activity, and only 6,8 % – high. High levels of physical activity is the lowest in the first year (6 %). The training slightly increased number of people with high levels of activity: on the second – 7,5 %; the third – 7,4% and in the fourth – 6,5 %. However, this growth is slight and does not significantly affect the number locomotions students. The chosen profession does not significantly affect the level of physical activity of young people. So, set the level of physical activity is insufficient and does not contribute to the maintenance of good functional condition of the body. Training effect has a high level of physical activity, which includes independent or specially organized physical exercise. But this component of physical activity is usually only in the form of mandatory training exercise. If there are no classes, then there is no high level of physical activity.
The Level of Physical Activity of Students in Higher Education
Keywords: фізична активність; IPAQ; студенти; physical activity; IPAQ; students